Igreja em saída: perspectivas do agir pastoral na cultura urbana brasileira - Bento, Willian (2025)
“Pastoral Theology” as an area of practical theology has had many forms and concrete objectives over time. As time has progressed, pastoral care has found fertile ground when it has assumed its perfect identity as an action of self-realization of the Church. In this way, it ceases to be a science focused solely on the internal training of its ministers, in an action predominantly of conservation of ecclesiastical structures, to assume a leading role in the elaboration of the most diverse processes of evangelization. With the Second Vatican Ecumenical Council, the Church became aware that it is necessary to return to its origins in order to resume dialogue with society. Returning to the first centuries, in which cities were great granaries for the proclamation of the Good News of Jesus of Nazareth, the conciliar Church has the desire to understand the city as a place to transmit the faith. In this sense, it is important to analyze the profound pastoral renewal that the Vatican Council fostered in the pastoral and evangelizing action of the Church itself, as well as to understand the City as a Locus Theologique, considering its most diverse configurations and manifestations. In this way, reflecting on the City and its peculiarities is the path through which one can think of an Urban Pastoral that considers the most diverse aspects for the elaboration of a practice that culminates in proximity, fraternity and the construction of a more humane, just and equal world. Thus, it is clear that the pontificate of Pope Francis has contributed considerably to the Church being in fact a spokesperson in this process of building a more fraternal society. By calling for a “Church that goes forth”, it makes us broaden pastoral perspectives in a dimension that goes beyond the walls of the Church and that must reach everyone